Adaptabilitas budaya Gen Z Surakarta: cultural intelligence, value congruence, and attitude toward culture in workplace.: Adaptabilitas budaya Gen Z Surakarta: cultural intelligence, value congruence, and attitude toward culture in workplace. - Adam Sasando; Ahmad Faris Bin Alias (Jurnal Bisnis Manajemen dan Akuntansi (BISMAK), 2024)
This study aims to analyze the influence of Cultural Intelligence, Value Congruence, and Attitude Toward Culture on Cultural Adaptability in Generation Z in Surakarta City. The approach used is quantitative descriptive with data analysis techniques using PLS-SEM through SmartPLS 3.0 software. The sample in this study amounted to 120 respondents who are part of the Gen Z population. The results of the study indicate that Attitude Toward Culture and Value Congruence have a positive and significant influence on Cultural Adaptability. Meanwhile, Cultural Intelligence does not have a significant effect. The R Square value of 0.650 indicates that the model has strong predictive ability. The model is also declared feasible to use based on the results of the SRMR and Q Square tests. These findings confirm that attitudes towards culture and equality values ??are important factors in increasing Generation Z's adaptability to cultural diversity in the workplace.